Contaminated land and its reclamation - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1997)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Contaminated land and the methods and legal controls governing its reclamation for subsequent development and use are of great current interest and concern. This volume in the Issues in Environmental Science and Technology series contains seven articles which treat the many aspects of this subject, ranging from risk assessment and risk management, through specific remediation methods and the evolution of government policy and controls, to analysis of the legal and technical features of specific environmental insurance policies. The chemistry of the non-ferrous heavy metals lead, zinc and cadmium is examined in relation to reclamation of superfund sites in the USA alongside a consideration of the role of the Welsh Development Agency in developing strategies for the recovery of derelict and contaminated land. An authoritative treatment of each of the topics is ensured by the particular expertise and distinction of the authors, and as such Contaminated Land and Its Reclamation will make an important contribution to the public debate on these issues. It will be essential reading for all those groups of people directly or indirectly involved, from consultants and their technical advisors, through developers, contractors and landowners, to local authorities and government agencies with responsibility for policy and its implementation in this area.
Keywords: Soil pollution -- Great Britain.; Soil remediation -- Great Britain.; Reclamation of land.; Great Britain.; elektronické knihy; electronic books